Hydraulic conductivity reduction during the recharge of the discharged groundwater: clogging pattern variation according to turbidity fluxes - Chinhoo Jung; Sang Hyun Kim; Yeon Gyoung Chu; Jaesang Lee; Jin-O Choi; Jaeshik Chung; Seunghak Lee (Results in Engineering, 2025)
Reinjection of the discharged groundwater at construction site into a nearby aquifer is considered as a beneficial approach. However, the suspended particles contained in the discharged groundwater might reduce the permeability of subsurface porous media, resulting in a rapid decrease in the reinjection efficiency. Therefore, to understand and predict the potential pore clogging during this particular process, we simulated the discharged groundwater recharging system and assessed the variation in hydraulic conductivities therein. The changes in relative hydraulic conductivities (K/K0) were observed in digital manometers-attached soil columns under various injection flux (Qsp) conditions. The relative hydraulic conductivities decreased more rapidly at a higher injection flux of suspended particles: K/K0 reached 0.1 in 13 h of injection when Qsp was 252 mg/h, while it took 550 h at the Qsp of 0.9 mg/h to attain the same K/K0. A critical time point, T0.1, at which the hydraulic conductivity decreased tenfold with respect to the initial, was estimated. Notably, two distinct patterns were observed in the transient variation in hydraulic conductivity depending on Qsp, an exponential reduction at higher Qsp and irregular pattern (e.g., temporary increases or plateaus) at relatively lower Qsp. A micro-computed tomography analysis revealed that the irregular patterns at lower Qsp were attributed to the seepage flow, which relocated the indigenous fine particles, changing the local porosity. However, at higher Qsp (e.g., 252 mg/h), pore clogging by the particles from the recharging water dominated this effect and resulted in a rapid and clear reduction in hydraulic conductivity.